Tad pili with adaptable tips mediate contact-dependent killing during bacterial predation - Julien Herrou; Laetitia My; Caroline L. Monteil; Marine Bergot; Rikesh Jain; Emmanuelle Martinez; Tâm Mignot (Nature Communications)
Abstract The predatory bacterium, Myxococcus xanthus, kills its prey by contact, using a putative Tight Adherence pilus, known as the Kil system, along with a protein complex resembling the basal body a type-III secretion system, named the “needleless” T3SS*. In this work, we provide direct evidence that Myxococcus polymerizes a Kil pilus at the prey contact site, which is constituted by the major pilin KilP. We also genetically demonstrate that the predation function of this pilus is linked to four different minor pilin complexes, which work in specific combinations to detect and kill phylogenetically diverse bacterial species. Structural models of the Kil pilus suggest that these minor pilin complexes form interchangeable “Tips”, exposing variable domains at the extremity of the pilus to interact with prey cells. Remarkably, the activity of these Tips also depends on the T3SS*, revealing a tight functional connection between the Kil system and the T3SS*. While these Tips are mostly restricted to predatory bacteria, genomic and structural analyses suggest that in other bacteria, including pathogens, Tad pili are also customized and functionalized by similar minor pilin complexes exposing variable domains.